IMPLEMENTATION OF KIRKPATRICK MODEL ON TECHNICAL GUIDELINES FOR TEACHER PERFORMANCE ASSESSMENT OF BASIC EDUCATION PERFORMANCE - Purnomo Hadi; Basuki Wibawa; Moch Sukardjo (International Journal of Education, Information Technology, and Others, 2020)
The research method uses an evaluation developed by Kirkpactrik. Data collection techniques using a questionnaire. Data analysis techniques using descriptive analysis. Participant research participants in the Teacher Performance Peenilian Technical Guidance in 2018. Technical Guidance on Teacher Performance Evaluation is carried out with the aim of providing teachers with skills to be able to use the Teacher Performance Assessment instrument to their peers. Evaluations at each important level are carried out to determine the level of effectiveness. Based on the results of the study obtained the following data; (1) the level of reaction of participants stated that the implementation of Bimtek was very good; (2) at the level of learning participants have a very good understanding of the PKG Guidance material. It was concluded that the implementation of the Teacher Performance Evaluation Technical Guidance was carried out in accordance with the implementation guidelines and objectives. The teacher has a very good level of understanding after following the Teacher Performance Assessment Technical Guidance. It is recommended that Technical Guidance on Teacher Performance Evaluation can be carried out in greater numbers so that the ratio between the assessed and the assessor gets smaller.